Creating an evergreen agriculture in Africa for food security and environmental resilience - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Project to double or even triple smallholder maize yields using sustainable techniques that regenerate the natural resource base without an overall increase in labour or the need to apply nitrogen fertilizers, using agroforestry techniques and conservation agriculture techniques. The Farmer Managed Natural Regeneration movement in Niger, Mali, and Burkina Faso, which has had tremendous impact, has influenced ICRAF, and they are seeking to build on/improve this.